Analisis Hubungan Bauran Pemasaran Terhadap Keputusan Konsumen dalam Pembelian Jamur Tiram di Rumah Jamur Nando Kota Pekanbaru - Rahmadhani, Putri; Yusmini, Yusmini; Maharani, Evy (Universitas Galuh, 2024)
Many people today are starting to realize the importance of healthy living by consuming oyster mushrooms. One of the oyster mushroom cultivation businesses in Pekanbaru City is the Rumah Jamur Nando. Rumah Jamur Nando must of course be able to face competition through a marketing mix strategy to attract consumers. The marketing mix is very important so that the Rumah Jamur Nando can overcome challenges in the market, keep up with market changes and can plan marketing activities in a more coordinated manner. This study aims to determine consumer assessments of the oyster mushroom marketing mix at the Rumah Jamur Nando and analyze the relationship between the marketing mix and consumer decisions in purchasing oyster mushrooms at the Rumah Jamur Nando. Sampling in this study using purposive sampling method with a sample size of 75 respondents. Data analysis using descriptive analysis and quantitative analysis using rank spearman. The results showed that consumer assessments of product variables, price, promotion, people (employees), physical evidence and processes in purchasing oyster mushrooms at the Rumah Jamur Nando resulted in an average with the agreed category, as well as the location variable with a fairly agreed category. The Spearman rank correlation coefficient value for all marketing mix variables at the Rumah Jamur Nando, namely product, price, promotion, place, people, process and physical evidence, is positive and there is a significant relationship with consumer decisions in purchasing oyster mushrooms.